Integrated analytical-field design method of multi-disc magnetorheological clutches for automotive applications - Krzysztof Kluszczyński; Zbigniew Pilch (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2021)
This study proposes a new integrated analytical-field design method for multi-disc magnetorheological (MR) clutches. This method includes two stages, an analytical stage (composed of 36 algebraic formulas) and a field stage based on the finite element method (FEM). The design procedure is presented systematically, step-by-step, and the results of the consecutive steps of the design calculations are depicted graphically against the background of the entire considered clutch. The essential advantage of the integrated method with this two-stage structure is the relatively high accuracy of the first analytical stage of the design procedure and the rapid convergence of the second field stage employing the FEM. The essence of the new method is the introduction of a yoke factor kY (the concept of which is based on the theory of induction machines) that determines the ratio of the total magnetomotive force required to magnetise the entire magnetic circuit of the clutch to the magnetomotive force required to magnetise the movement region. The final value, the yoke factor kY is determined using loop calculations. The simplicity of the developed design method predisposes its use in optimisation calculations. The proposed method can also be adapted to other MR devices analysed in shear mode.